Epidermal growth factor receptor-tyrosine kinase inhibitor (gefitinib) augments pneumonitis, but attenuates lung fibrosis in response to radiation injury in rats - Toyoda, Yuko; Yuasa, Shino; Aono, Yoshinori; Suzuka, Chiyuki; Tezuka, Toshifumi; Tani, Kenji; Miyake, Keiko; Kishi, Jun; Hanibuchi, Masaki; Sone, Saburo; Nishioka, Yasuhiko; Kakiuchi, Soji (The Journal of Medical Investigation, 2012)
Background: Gefitinib, an inhibitor of epidermal growth factor receptor (EGFR) tyrosine kinase, has been reported to be associated with interstitial lung disorders, and their high incidence and mortality have become a matter of great concern, especially in Japan. In this study, we investigated the effect of gefitinib on different phases of radiation-induced lung disorders in an experimental model. Methods: The thoraxes of Wistar rats were irradiated on day 1 with a single X-ray dose of 20 Gy, and gefitinib (50 mg/kg/day) was orally administered from day 1 to 14. The rat lungs were harvested on days 15 and 57 and the bronchoalveolar lavage (BAL) was performed. Results: Gefitinib treatment increased the infiltration of inflammatory cells, which produced more pro-inflammatory cytokines (IL-6, IL-1β), in the lungs of the irradiated rats on days 15 and 57, while gefitinib treatment reduced collagen content of the lungs in irradiated rats and decreased proliferation and EGFR expression in the lung fibroblasts from irradiated rats on day 57. Conclusions: In irradiated rats, gefitinib treatment augmented lung inflammation, including inflammatory cell infiltration and pro-inflammatory cytokine expression, while gefitinib treatment attenuated fibrotic lung remodeling due to the inhibition of lung fibroblast proliferation. J. Med. Invest. 59: 174-185, February, 2012